There is no association between combined oral hormonal contraceptives and depression: a Swedish register‐based cohort study. (9th December 2021) - Lundin, C; Wikman, A; Lampa, E; Bixo, M; Gemzell‐Danielsson, K; Wikman, P; Ljung, R; Sundström Poromaa, I
Abstract : Objective: To investigate whether users of hormonal contraceptives (HCs) are at increased risk of depression compared with non‐users. Design: Register‐based cohort study. Setting: Sweden. Sample: Women aged 15–25 years between 2010 and 2017 with no prior antidepressant treatment, psychiatric diagnose or contraindication for HCs ( n = 739 585). Methods: Women with a prescription of HC were identified via the Swedish Prescribed Drug Register (SPDR). Relative risks (RRs) for first depression diagnosis in current HC‐users compared with non‐users were modelled by Poisson regression. Adjustments included age, medical indication for HC‐use and parental history of mental disorders, among others. Main outcome measures: Depression, captured by a redeemed prescription of antidepressant treatment, or a first depression diagnosis in the SPDR and the National Patient Register. Results: Compared with non‐users, women on combined oral contraceptives (COCs) and oral progestogen‐only products had lower or no increased risk of depression, relative risk (RR) 0.89 (95% CI 0.87–0.91) and 1.03 (95% CI 0.99–1.06) after adjustments, respectively. Age‐stratified analyses demonstrated that COC use in adolescents conferred no increase in risk (RR 0.96, 95% CI 0.93–0.98), whereas use of progestogen‐only pills (RR 1.13, 95% CI 1.07–1.19), contraceptive patch/vaginal ring (RR 1.43, 95% CI 1.30–1.58), implant (RR 1.38, 95% CI 1.30–1.45) or a levonorgestrel intrauterine device (RR 1.59, 95% CI 1.46–1.73) were associated with increased risks. Conclusions: This study did not find any association between use of COCs, which is the dominating HC in first time users, and depression. Non‐oral products were associated with increased risks. Residual confounding must be addressed in the interpretation of the results. Tweetable abstract: There is no association between combined hormonal contraceptives and depression. Tweetable abstract: There is no association between combined hormonal contraceptives and depression.